The role of media and retailer message recall on Malaysian male perceptions of e-cigarette use: the 2016 national study of e-cigarettes prevalence - Lei, Hum Wee; Guat, Hiong Tee; Mei, Caryn Hsien Chan; Draman, Samsul; Ab Rahman, Jamalludin; Bee, Kiau Ho; Miaw, Jane Yn Ling; Kuang, Hock Lim; Mohd Yusoff, Muhammad Fadhli; Baharom, Nizam; Robson, Noorzurani; Kartiwi, Mira; et al. (Sage Publications Inc, 2022)
This study examined the perceptions of current smokers on electronic cigarette (EC) use, after exposure to information on EC use and its potential harms from various media and retail outlets. This cross-sectional study is a sub-analysis of the National Study of Electronic Cigarettes Prevalence (N = 4289) using the multi-stage stratified sampling method. Respondents were interviewed face-to-face by a trained data collector using a structured questionnaire printed in both Bahasa Malaysia and English. The analysis included 376 males who smoked conventional cigarettes and/or used ECs and reported ever seeing messages on ECs/vape in various platforms were analyzed using weighted simple and multiple logistic regression. Our findings showed different media types resulted in differing perceptions among smokers towards EC use especially between social media and conventional media. Those exposed to messages promoting EC in social media had higher odds of believing that ECs help people quit smoking (OR: 2.28), the urge to smoke is reduced by ECs (OR: 1.86), ECs are more effective than medication for quitting smoking (OR: 1.96), breathing is improved after using ECs (OR: 2.85), the smell of EC is better than a tobacco cigarette (OR: 2.73), and ECs should be regulated rather than banned completely (OR: 3.08). Vape shops, social, and conventional media provided very different perceptions among smokers towards EC use. Beyond using traditional communication channels, EC promoters have successfully utilized social media to promote ECs among smokers.